Use of complementary and alternative medicine by patients with dermatological disorders in western part of India: a prospective study - Gohil, Nayana J. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: This study was aimed in assessing the prevalence and pattern of CAM in patients with dermatological disorders. Methods: This cross sectional study was carried out at outpatient department of Dermatology at tertiary care teaching hospital. Data was collected with help of questionnaire which contained sociodemographic details and details of use of CAM if any by the attending patients. Data was analysed for sociodemographic and clinical character, pattern of use of CAM, source of information and reasons for using CAM. Results: Mean age of participants was 29.29±20.25 (Mean±SD) years and 102 (46.54%) users were women. Highly educated patients (49.25%) were the most frequently CAM users. Below 20 years (57.84%) youngsters were the frequent CAM users. About 45.19% patients were belonging to rural area of community. Acne vulgaris was the commonest condition for CAM use. Folk medicines (70.73%) were the most frequent used CAM. Advised by friends/relatives was the commonest source of information. About 80.49% patients had not informed to their physician about the use of CAM. None of the patients had knowledge of adverse effect of CAM. Conclusions: Use of CAM is very common in dermatological disorders, youngsters and literate were the most common CAM users. Combined administration of herbs with prescription drugs may increase or decrease the pharmacological or toxicological effects of either compound.